Capillary discharge tabletop soft X-ray lasers reach new wavelengths and applications - Uspenskii, Y. A., author; Vinogradov, A., author; Artioukov, I. A., author; Ozols, A., author; Kanizay, K., author; Marconi, M., author; Filevich, J., author; Seminario, M., author; Benware, B., author; Frati, M., author; Rocca, Jorge J., author; Académie des sciences/Éditions scientifiques et médicales Elsevier SAS, publisher (Colorado State University. Libraries, 2000)
For many years, researchers have envisioned the development of compact high repetition rate tabletop soft X-ray lasers that could be routinely used in application in numerous disciplines. With demonstrated average powers of several mW and mJ-level pulse energy at 46.9 nm, capillary discharge-pumped lasers are the first compact lasers to reach this goal. In this paper we summarize the development status of high repetition rate tabletop soft X-ray lasers based on capillary discharge excitation, and give examples of their successful use in several applications. Results of the use of a capillary discharge pumped 46.9 nm laser in dense plasma interferometry, soft X-ray reflectometry for the determination of optical constants, and laser ablation are described. The observation of lasing at 53 nm line in Ne-like Cl with output pulse energy up to 10 μJ is also reported.